Complement membrane attack complex is an immunometabolic regulator of NLRP3 activation and IL-18 secretion in human macrophages - Jimenez-Duran, Gisela; Kozole, Joseph; Peltier-Heap, Rachel; Dickinson, Eleanor R.; Kwiatkowski, Christopher R.; Zappacosta, Francesca; Annan, Roland S.; Galwey, Nicholas W.; Nichols, Eva-Maria; Modis, Louise K.; Triantafilou, Martha; Triantafilou, Kathy; et al. (Frontiers in Immunology, 2022)
The complement system is an ancient and critical part of innate immunity. Recent studies have highlighted novel roles of complement beyond lysis of invading pathogens with implications in regulating the innate immune response, as well as contributing to metabolic reprogramming of T-cells, synoviocytes as well as cells in the CNS. These findings hint that complement can be an immunometabolic regulator, but whether this is also the case for the terminal step of the complement pathway, the membrane attack complex (MAC) is not clear. In this study we focused on determining whether MAC is an immunometabolic regulator of the innate immune response in human monocyte-derived macrophages. Here, we uncover previously uncharacterised metabolic changes and mitochondrial dysfunction occurring downstream of MAC deposition. These alterations in glycolytic flux and mitochondrial morphology and function mediate NLRP3 inflammasome activation, pro-inflammatory cytokine release and gasdermin D formation. Together, these data elucidate a novel signalling cascade, with metabolic alterations at its centre, in MAC-stimulated human macrophages that drives an inflammatory consequence in an immunologicaly relevant cell type.